Long-term clinical results of per-oral endoscopic myotomy (POEM) for achalasia: First report of more than 10-year patient experience as assessed with a questionnaire-based survey - Onimaru, Manabu; Inoue, Haruhiro; Fujiyoshi, Yusuke; Abad, Mary Raina Angeli; Nishikawa, Yohei; Toshimori, Akiko; Shimamura, Yuto; Tanabe, Mayo; Sumi, Kazuya; Ikeda, Haruo (Endoscopy International Open, 2021)
Background and study aims Since per-oral endoscopic myotomy (POEM) was introduced in 2010, it has become accepted as one of the standard treatments for esophageal achalasia worldwide. This study aimed to present long-term clinical results of POEM over 10 years and evaluate the technique and outcomes at the institution where it was first used in clinical settings.Patients and methods Questionnaire-based surveys were sent to patients who received POEM in our institution from September 2008 to May 2010. Patient demographics and procedural outcomes and open-ended questions were posed about the postoperative courses, including symptom improvement and recurrence, additional treatments, and post-POEM gastroesophageal reflux disease (GERD) symptoms. Achalasia symptoms and post-POEM GERD symptoms were evaluated with Eckhardt scores and GerdQ systems, respectively.Results Thirty-six consecutive POEMs were performed in that period and 10-year follow-up data were obtained from 15 patients (41.7 %). Although four cases (26.7 %) required additional pneumatic balloon dilatation (PBD), reduction in post-Eckardt scores were observed in 14 cases (93.3 %). GerdQ score was positive in one patient (6.7 %). Proton pump inhibitors (PPI) were taken by four patients (26.7 %) and their symptoms were well-controlled. Conclusions Clinical results of POEM over 10 years were favorable regardless of various factors. Symptoms improved even in patients who required additional treatments, suggesting that POEM plays a significant role in treatment of achalasia.